PolyTile 2.0: Programmable microtextured ceramic architectural tiles embedded with environmentally responsive biofunctionality. (March 2021) - Zhang, Viola; Rosenwasser, David; Sabin, Jenny E
PolyTile 2.0 interrogates the potential of programmable biofunctionalities in our constructed architectural environments through the development of advanced ceramic bio-tiles. These tiles utilize novel patterning techniques and hydrogel biomaterials to tune surface conditions at the micro- and macroscale. This trans-disciplinary work builds upon recent advancements in the fields of three-dimensional printing, digital ceramics, materials science, bioengineering, chemical biology, and architecture. PolyTile 2.0 enables designers and architects to implement biofunctionality and microscale patterning fittingly and with the ability to continuously adjust design iterations across scales. The refinement utilizes glazing strategies as a directable fluidic device and biocompatible hydrogels as a sensing platform to further developments in responsive built environments. This article outlines methods for the production of bulk-scale hydrogel materials, stereolithography-based three-dimensional printed ceramic tiles, and scalable glazing techniques, which bring building-scale application of this technology to the foreground.